The Saliency of Snake Scales and Leopard Rosettes to Infants: Its Relevance to Graphical Patterns Portrayed in Prehistoric Art - Coss, Richard G.; Charles, Eric P. (Frontiers in Psychology, 2021)
Geometrically arranged spots and crosshatched incised lines are frequently portrayed in prehistoric cave and mobiliary art. Two experiments examined the saliency of snake scales and leopard rosettes to infants that are perceptually analogous to these patterns. Experiment 1 examined the investigative behavior of 23 infants at three daycare facilities. Four plastic jars (15×14.5cm) with snake scales, leopard rosettes, geometric plaid, and plain patterns printed on yellowish-orange paper inside were placed individually on the floor on separate days during playtime. Fourteen 7–15-month-old infants approached each jar hesitantly and poked it before handling it for five times, the criterion selected for statistical analyses of poking frequency. The jars with snake scales and leopard rosettes yielded reliably higher poking frequencies than the geometric plaid and plain jars. The second experiment examined the gaze and grasping behavior of 15 infants (spanning 5months of age) seated on the laps of their mothers in front of a table. For paired comparisons, the experimenter pushed two of four upright plastic cylinders (13.5×5.5cm) with virtually the same colored patterns simultaneously toward each infant for 6s. Video recordings indicated that infants gazed significantly longer at the cylinders with snake scales and leopard rosettes than the geometric plaid and plain cylinders prior to grasping them. Logistic regression of gaze duration predicting cylinder choice for grasping indicated that seven of 24 paired comparisons were not significant, all of which involved choices of cylinders with snake scales and leopard rosettes that diverted attention before reaching. Evidence that these biological patterns are salient to infants during an early period of brain development might characterize the integration of subcortical and neocortical visual processes known to be involved in snake recognition. In older individuals, memorable encounters with snakes and leopards coupled with the saliency of snake scales and leopard rosettes possibly biased artistic renditions of similar patterns during prehistoric times.